قانونِ وقف املاک علاقہ جات وفاقی دارالحکومت اسلام آباد 2020 کی دفعات کا تنقیدی مطالعہ: critical study of the provisions of Islamabad Capital Territory Waqf Property Act 2020 - Syed Hayatullah Agha,; Dr. Muhammad Atif Aslam Rao, (MEI, 2025)
Waqf is one of the basic rights that Shariah gives to a person in his unmovable possession. A Waqf is a voluntary, perpetual, irrevocable dedication of a portion of one’s property. Its main conditions are non-transfer of ownership and use in the public interest. The main uniqueness or privilege of waqf practice lies in the concept of separation between the right of ownership and the right of use. Although the term has been voiced in the Shariah, this procedure was also practiced from ancient times and Islam kept with some limits and restrictions. To accomplish this in a legal way, the law related to waqf property in Islamabad Capital Territory Pakistan was formulated in 2020 at the request of the Financial Action Task Force. The article under review is actually a research based critical study of the ICT Waqf Property Act 2020. According to the constitution, all laws to be made in Pakistan must be in accordance with the Qur'an and Sunnah. The fact that some clauses in said act are opposing to Shariah standards emphasizes the need to review the flaws and make it according to Shariah Standards. The research concludes that although this act has many beneficial effects, some clauses are in conflict with the Shariah. In which, the clauses related to the ownership of waqf property, to the non-differentiation of waqf property and the benefits derived from it, to the appointment of the waqf administrator and his role and to the illegal occupants need to be reviewed. It is essential to eradicate the imperfections in this act so that it imitates to Shariah teachings and produces extensive effects.